2005
DOI: 10.1063/1.2077841
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotube quantum dots fabricated on a GaAs∕AlGaAs two-dimensional electron gas substrate

Abstract: Single-wall carbon nanotube (SWCNT) quantum dots have been fabricated on a GaAs∕AlGaAs two-dimensional electron gas (2DEG) substrate, and the single electron transport measurements have been carried out at 2.8 K and 22 mK with the 2DEG used as a gate. It was demonstrated that the gating by the 2DEG could be switched on and off by controlling a quantum point contact fabricated between the dot and the Ohmic contact to the 2DEG gate. The unique combination of the SWCNT dot and the 2DEG may open a door to realize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…The color coordinate of the as-fabricated WLEDs at (0.33, 0.28) was very close to that of the pure white light. The curing flexible 100 wt % SRs with the shore hardness at 13 A were expected to have potential application in flexible optoelectronic devices because a few groups have reported that kind of work based on CDs, graphene, and carbon nanotubes. …”
Section: Introductionmentioning
confidence: 99%
“…The color coordinate of the as-fabricated WLEDs at (0.33, 0.28) was very close to that of the pure white light. The curing flexible 100 wt % SRs with the shore hardness at 13 A were expected to have potential application in flexible optoelectronic devices because a few groups have reported that kind of work based on CDs, graphene, and carbon nanotubes. …”
Section: Introductionmentioning
confidence: 99%
“…SWCNT quantum-dot devices may open other device designs and may have interfaces to outside electronic circuits by combining them with the GaAs/ AlGaAs two-dimensional electron gas system 41 and Si metal-oxide semiconductor field-effect transistors ͑MOSFETs͒. In our present study, we showed that the carbon nanotubes are a promising building block for extremely small quantum-dot-based nanodevices that are not easily fabricated by standard microfabrication techniques.…”
Section: Discussionmentioning
confidence: 60%
“…Next, we show another mechanism to detect the THz photons [69]. A SWCNT SET was fabricated on top of the GaAs/AlGaAs 2DEG wafer [70].…”
Section: Quantum Thz Detectionmentioning
confidence: 99%